2014
DOI: 10.1210/en.2014-1318
|View full text |Cite
|
Sign up to set email alerts
|

Blocking Ligand Occupancy of the αVβ3 Integrin Inhibits the Development of Nephropathy in Diabetic Pigs

Abstract: Hyperglycemia stimulates secretion of αVβ3 ligands from vascular cells, including endothelial cells, resulting in activation of the αVβ3 integrin. This study determined whether blocking ligand occupancy of αVβ3 would inhibit the development of diabetic nephropathy. Ten diabetic pigs received an F(ab)2 fragment of an antibody directed against the extracellular domain of the β3-subunit, and 10 received a control IgG F(ab)2 for 18 weeks. Nondiabetic pigs excreted 115 ± 50 μg of protein/mg creatinine compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 44 publications
6
37
0
Order By: Relevance
“…12,29 In animal models of diabetic kidney disease, blockade of β 3 integrin with the use of a monoclonal antibody was protective. 12,31,32 In addition to its role in the activation of α V β 3 integrin on podocytes, suPAR may mediate kidney injury through several molecular mechanisms. For example, CD40 autoantibodies have been implicated in modifying the effect of suPAR in focal segmental glomerulosclerosis, 33 whereas levels of acid sphingomyelinase-like phosphodiesterase 3b have been implicated in modulating the effect of suPAR in diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…12,29 In animal models of diabetic kidney disease, blockade of β 3 integrin with the use of a monoclonal antibody was protective. 12,31,32 In addition to its role in the activation of α V β 3 integrin on podocytes, suPAR may mediate kidney injury through several molecular mechanisms. For example, CD40 autoantibodies have been implicated in modifying the effect of suPAR in focal segmental glomerulosclerosis, 33 whereas levels of acid sphingomyelinase-like phosphodiesterase 3b have been implicated in modulating the effect of suPAR in diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, loss of podocin expression is not an inevitable consequence of integrin signaling in podocytes. Regardless of how αvβ3-integrin is activated by circulating factors, several studies have shown efficacy of αvβ3-integrin antagonists in animal models of proteinuric diseases [5,62,63]. As an aside, we should note here that human TNF is only able to activate the type 2 TNF receptor in mice [64], but that receptor is already thought to play a role in driving kidney disease [65].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, an α v β 3 integrin antibody has been shown to prevent the development of DN in diabetic pigs (Maile et al. ) and diabetic rats (Maile et al. ).…”
Section: Introductionmentioning
confidence: 99%